A hydrogen bond-modulated soft nanoscale water channel for ion transport through liquid–liquid interfaces. Issue 42 (13th October 2021) - Wen, Boyao; Sun, Chengzhen; Luo, Zhengyuan; Lu, Xi; Wang, Haibo; Bai, Bofeng
Abstract : We identify a hydrogen bonding-modulated water channel for ions transport through the interfaces and decane phase. Abstract : Ion transport through interfaces is of ubiquitous importance in many fields such as electrochemistry, emulsion stabilization, phase transfer catalysis, liquid–liquid extraction and enhanced oil recovery. However, the knowledge of interfacial structures that significantly affect ion transport through liquid–liquid interfaces is still lacking due to the difficulty of observing nanoscale interfaces. We studied here the evolution of interfacial structures during ion transport through the decane–water interface under different ionic concentrations and external forces using molecular dynamics simulations. The roles of hydrogen bonds in ion transport through interfaces are revealed. We identified a soft nanoscale channel during ion transport through liquid–liquid interfaces and the decane phase under specific external force. The stability of the water channel and the ion transport velocity both increase with ionic concentration due to the layered ordering structures of the water near the channel surface. We observed that the stability and connectivity of the water channel in the decane phase are remarkably improved both by the high increase of the number of hydrogen bonds in the water channel with increasing ionic concentration, and by the conformational change in water molecules near the water channel surface. Our discovery of a soft nanoscale water channel by molecular simulations implies that there is a potential stable passage for ion transport through liquid–liquid interfaces.